2009
DOI: 10.1016/j.juro.2008.11.109
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Evaluation of Active Surveillance for Low Risk Prostate Cancer

Abstract: Purpose For select men with low-risk prostate cancer, active surveillance (AS) is more often being considered a management strategy. In a multicenter retrospective study we evaluated the actuarial rates and predictors of remaining on AS, incidence of cancer progression, and pathologic findings of delayed radical prostatectomy. Methods A cohort of 262 men from four institutions met the following inclusion criteria: age ≤75, PSA ≤10 ng/ml, clinical stage T1-T2a, biopsy Gleason sum ≤6, ≤3 positive cores at diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(22 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The surveillance prostate biopsy has been regarded as useful evaluation tool for AS. However, the sampling error of surveillance biopsy is well documented in many AS studies [18][19][20]. Berglund et al [18] found upgrading in 27 % of the patients undergoing immediate restaging biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surveillance prostate biopsy has been regarded as useful evaluation tool for AS. However, the sampling error of surveillance biopsy is well documented in many AS studies [18][19][20]. Berglund et al [18] found upgrading in 27 % of the patients undergoing immediate restaging biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Berglund et al [18] found upgrading in 27 % of the patients undergoing immediate restaging biopsy. Eggener et al [19] found a 30 % rate of upgrading on restaging biopsy before initiation of surveillance-based treatment. van den Bergh et al also reported that a 22 % of upgrading with re-biopsy at 1 year in a large cohort of more than 500 men undergoing active surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence in Northern and Western Europe is the highest in the European Union, and rates in Eastern and Southern Europe are steadily increasing [3]. The management of localized prostate cancer is challenging for urologists in terms of both treatment costs and risk of over-diagnosis, which can lead to over-treatment and secondary complications that outweigh the potential benefits [4]. …”
Section: Introductionmentioning
confidence: 99%
“…In final pathology reported Gleason sum was ≥7, while positive surgical margin rate was 8%, extrapostatic extension rate was 15%, and positive lymph node rate was 4%. [12] In the Johns Hopkins series which had a very strict on patient selection criteria, lymph node positivity rate was 2.1% (2/96). [13] In the current study lymph node metastasis was detected following RP only in one patient with a Gleason sum of 9.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, "rebiopsy within the first 3 months" was included in the inclusion criteria to confirm tumor histopathology. [12] In another study by Berglund et al[ 14] on the issue, rebiopsies were performed in 104 patients scheduled for AS at median 6 months after initial biopsy. Increase in grade and/or stage of the tumor was 27% (28/104), and these patients were excluded from the AS protocol.…”
Section: Discussionmentioning
confidence: 99%